Enteric methane in grazing beef cattle under full sun, and in a silvopastoral system in the Amazon - Frota, Marcílio Nilton Lopes; Carneiro, Maria Socorro de Souza; Pereira, Elzânia Sales; Berndt, Alexandre; Frighetto, Rosa Toyoko Shiraishi; Sakamoto, Leandro Sannomiya; Moreira Filho, Miguel Arcanjo; Cutrim Júnior, José Antonio Alves; Carvalho, Geraldo Magela Cortês (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the quality of pasture and enteric methane (CH4) emission of Curraleiro Pé-duro x Nellore cattle in a pasture of Megathyrsus maximus 'Mombaça', both in full sun and in a consortium with babassu palms (Attalea spp.) in the Amazonian biome. The experimental design was completely randomized, with six steers per system, and the evaluations were done during the dry period (2015) and rainy period (2016). In comparison to forage in the full sun system, forage in the silvopastoral system showed, in the dry period, higher levels of crude protein, ether extract, total digestible nutrient, and in vitro digestible organic matter, and lower levels of dry matter, neutral detergent fiber, and total carbohydrate (TCHO). In the rainy period, forage in the silvopastoral system showed higher levels of crude protein and a reduction of nonfibrous carbohydrate and TCHO. The CH4 emissions were similar in both systems within the same period, and ranged from 44.0 to 74.2 kg per year per animal. During the dry period, the emission per kilogram of dry ingested matter and the loss of gross energy as methane were lower in the silvopastoral system. During the rainy period, the emissions were similar in both systems. The silvopastoral system yields forage with good quality in the dry period, and considering both periods, it is more efficient (emission of CH4 per daily weight gain) than the system in full sun.